Facial Biometrics for Attendance System - D.M.V. Priya; P. Srinivasa Vinay; K. Roopesh; T. Prabhu Teja; B. Jagadeesh (International Journal of Electrical and Communication Engineering Technology, 2024)
This paper discusses the necessity for effective student attendance management systems by proposing a smart attendance management system utilizing biometric technology. It is well recognised that manually recording attendance is time-consuming and error prone. In this study, we propose a Facial Biometrics attendance system that automates attendance process without requiring human intervention. The system consists of a camera placed in the classroom to take pictures of the pupils. Subsequently, the captured images are analyzed for facial features through the implementation of the Histogram of Oriented Gradients (HOG) algorithm for precise face detection. After identification, the K-Nearest Neighbour (KNN) classifier is used to identify the faces. Then marked as present or absent upon the recognition results, and these detected facial records are securely stored within a database for future reference and analysis. The Technology allows Users to have access to real-time attendance data and can generate monthly attendance reports effortlessly. By employing this methodology, the system achieves efficiency and stability, resulting in a significant reduction in classroom attendance management costs
Keywords: Facial biometrics; HOG Algorithm; K-nearest neighbor; images